THE GREEK EXPERIENCE FROM THE EU MEMBERSHIP - Tsounis, Nicholas (Journal of European Economy, 2018)
The paper presents further quantitative estimates of the trade and welfare effects of the entrance of Greece into the E.U. and formulates a tool for assessing the impact of the candidate countries’ accession to the E.U. Static and dynamic effects of the entrance of Greece into the EU are examined. Upon the examination of the static effects, it has been shown that there was a «net» trade creation of about 1.6 billion U.S dollars, which accounted for approximately 4.4% of the GDP produced in the year before the accession. It was also found out that 86% of the total trade creation was internal trade creation while 84% of the total trade diversion was external trade diversion. These results accord with the theory of the customs union. As a result of examining the dynamic effects it has been found out that the entrance of Greece into the E.U. was mixed in the various sectors. It was found that for about two thirds of the examined sectors, the integration of Greece into the E.U. has been desirable. In general, however, the integration indexes found are very close to unity showing that the dynamic effects of the entrance of Greece into the E.U. have been minimal.